2000
DOI: 10.1136/jcp.53.11.813
|View full text |Cite
|
Sign up to set email alerts
|

Autoantigens in primary biliary cirrhosis

Abstract: The automimmune liver disease primary biliary cirrhosis (PBC) is characterised by serum autoantibodies directed at mitochondrial and nuclear antigens (seen in most patients and a subset of patients, respectively). The antimitochondrial antibodies (AMA) characteristic of PBC are directed at members of the 2-oxoacid dehydrogenase components of multienzyme complexes; in particular, the E2 and E3 binding protein (E3BP) components of the pyruvate dehydrogenase complex (PDC). The presence of autoantibodies reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 129 publications
(81 reference statements)
2
21
1
Order By: Relevance
“…Primary biliary cirrhosis is a kind of autoimmune disease caused by the impairment of the host's immune tolerance to its mitochondrial antigen by an as yet undetermined mechanism [12]. We established a PBC animal model by injecting C57BL/6 mice with polyI:C and found that AICD in splenic and hepatic CD4?…”
Section: Discussionmentioning
confidence: 99%
“…Primary biliary cirrhosis is a kind of autoimmune disease caused by the impairment of the host's immune tolerance to its mitochondrial antigen by an as yet undetermined mechanism [12]. We established a PBC animal model by injecting C57BL/6 mice with polyI:C and found that AICD in splenic and hepatic CD4?…”
Section: Discussionmentioning
confidence: 99%
“…The major mitochondrial antigens reacting with AMA have been identified as components of the 2-oxoacid (or a-ketoacid) dehydrogenase complexes contain pyruvate dehydrogenase (PDH), branch chain 2-oxo acid dehydrogenase (BCOADH), 2-oxoglutarate dehydrogenase (OGDH), and protein X, each of which contains multiple copies of catalytic components that catalyze the consecutive steps in the oxidative decarboxylation of 2-oxo acid substrates. PBC sera also recognize other liver antigens: centromere antigens and multiple antinuclear ''nuclear dots'' antigen (3)(4)(5).…”
Section: Introductionmentioning
confidence: 97%
“…PBC is characterized by progressive inflammatory damage to the biliary epithelial cells, elevated biliary tract enzymes and positive anti-mitochondrial antibody (AMA). PBC is known to frequently have other autoimmune phenomena (3,4). Anti-platelet autoantibodies are detected in approximately 40% of patients and it is assumed that the immune-mediated destruction of platelets contributes to the thrombocytopenia in a considerable portion of patients with PBC (5,6).…”
Section: Introductionmentioning
confidence: 99%